2020
DOI: 10.1002/jat.3918
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to arsenite enhances influenza virus infection in cultured cells

Abstract: Arsenic is a ubiquitous environmental toxicant that has been associated with human respiratory diseases. In humans, arsenic exposure has been associated with increased risk of respiratory infection. Considering the existing epidemiological evidence and the well‐established impact of arsenic on epithelial cell biology, we posited that the effect of arsenic exposure in epithelial cells could enhance viral infection. In this study, we characterized influenza virus A/WSN/33 (H1N1) infection in Madin‐Darby Canine K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…These data generally are in agreement with the earlier observation of impaired antiviral response and higher pulmonary virus titer in a model of H1N1 influenza infection in C57BL/6J mice ( Kozul et al, 2009 ). Moreover, chronic arsenite exposure significantly increased susceptibility to H1N1 influenza infection through sialic acid binding as well as decreased efficiency of oseltamivir ( Amouzougan et al, 2020 ). In addition, prenatal As exposure significantly aggravated influenza A-induced pulmonary inflammation ( Ramsey et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…These data generally are in agreement with the earlier observation of impaired antiviral response and higher pulmonary virus titer in a model of H1N1 influenza infection in C57BL/6J mice ( Kozul et al, 2009 ). Moreover, chronic arsenite exposure significantly increased susceptibility to H1N1 influenza infection through sialic acid binding as well as decreased efficiency of oseltamivir ( Amouzougan et al, 2020 ). In addition, prenatal As exposure significantly aggravated influenza A-induced pulmonary inflammation ( Ramsey et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“… 63 Furthermore, acute phase replication of influenza virus is enhanced in cells exposed to arsenite. 64 However, little is known about how stress affects viruses at the chronic infection phase. Exceptions are studies of social stress reported to cause reactivation of latent DNA virus, e.g., HSV-1, 2 and of oxidative stress leading to reactivation of HIV-1.…”
Section: Discussionmentioning
confidence: 99%
“…G3BP1) to promote viral gene expression (Bonenfant et al, 2019). Furthermore, acute phase replication of influenza virus is enhanced in cells exposed to arsenite (Amouzougan et al, 2020). However, little is known about how stress affects viruses, especially RNA viruses, at the chronic infection phase.…”
Section: Discussionmentioning
confidence: 99%